KAMPANYE KOMUNITAS INDONESIA FEMINIS DALAM MENSOSIALISASIKAN TENTANG UNDANG-UNDANG TINDAK PIDANA KEKERASAN SEKSUAL (UU TPKS) MELALUI AKUN INSTAGRAM @INDONESIAFEMINIS - Ratna Setyaraharjoe; Julyanto Ekantoro; Anindita Putri Pratiwi (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2023)
The phenomenon of sexual violence always haunts society, especially Indonesian women. In connection with this phenomenon, the Indonesian Feminist Community as a community or network that spreads the ideology of feminism and gender equality makes this discourse a tool in building campaigns for the Sexual Violence Act (TPKS Law) and also provides efforts to understand the public. Based on the data that has been obtained, that in addition to being a forum for campaigning for the Law on Sexual Violence (TPKS Law) and also educating the public about the many forms of sexual violence. The Indonesian Feminist Community is also very good at utilizing social media, especially the Instagram platform to network with several other communities who are also campaigning for the Sexual Violence Act (UU TPKS) to help share these posts through the Indonesian Feminist Community's Instagram platform. Keyword: TPKS Law, Campaign, Feminist Community's, Sexual Violence